2006
DOI: 10.1080/09513590601005805
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fibrinolytic and metabolic system parameters in obese patients with polycystic ovary syndrome and women with simple obesity

Abstract: The present study aimed to assess the fibrinolytic and metabolic system parameters in obese patients with polycystic ovary syndrome (PCOS) and to compare them in obese PCOS patients and women with simple obesity. We studied 19 obese women with PCOS (age: 25.1 +/- 4.6 years, body mass index (BMI): 34.7 +/- 3.9 kg/m2; mean +/- standard deviation) and 20 age- and BMI-matched ovulatory controls. We measured blood levels of 17beta-estradiol, testosterone, prolactin, luteinizing hormone (LH), follicle-stimulating ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
1
11
1
1
Order By: Relevance
“…In contrast to normal weight subjects, overweight/ obese patients with PCOS had higher PAI-1 levels than BMI-matched controls, a finding that concurs with most previous studies [13][14][15][16]23]. However, plasma PAI-1 levels did not correlate with markers of IR in overweight/obese women with PCOS in our study and this is in contrast to previous reports [13,14,24,25].…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast to normal weight subjects, overweight/ obese patients with PCOS had higher PAI-1 levels than BMI-matched controls, a finding that concurs with most previous studies [13][14][15][16]23]. However, plasma PAI-1 levels did not correlate with markers of IR in overweight/obese women with PCOS in our study and this is in contrast to previous reports [13,14,24,25].…”
Section: Discussioncontrasting
confidence: 57%
“…It has been well established that both overweight and android obesity with increased waist circumference constitute risk factors for CVD (34)(35)(36)(37)(38). It is also known that for the general population, the older the age and the higher the BMI, the greater the risk of thromboembolic phenomena (39)(40)(41)(42)(43)(44). A recent relevant study from Denmark reported that PCOS was associated with a twofold greater risk of stroke and thrombosis, whereas there was no increased risk of other CVD (4).…”
Section: Discussionmentioning
confidence: 99%
“…These findings might elucidate some discrepancies regarding fibrinolytic activity in PCOS, as earlier studies indicate both increased PAI-1 activity [15,100,101,160] and normal PAI-1 activity in PCOS patients [102,103] [159]. Thus, it is plausible studies indicating no difference in PAI-1 activity have included a more heterogeneous population of PCOS patients with regard to hyperandrogenism.…”
mentioning
confidence: 75%
“…Increased mass concentration of tPA, as a marker of endothelial disturbances, is possibly a better predictor for coronary heart mortality [98] than PAI-1 activity and is specifically associated with myocardial infarction in young women [99]. The triad obesity, raised triglycerides and, raised insulin levels is the most consistent predictor of impaired fibrinolysis and is often found in PCOS women [15,[100][101][102][103]. Earlier studies on PCOS women suggest both increased and normal levels of PAI-1 activity [15,[100][101][102][103], while studies on tPA-mass in PCOS patients are less ambiguous with increased levels [104][105][106], although at least one study reported unchanged levels [107].…”
Section: Fibrinolysismentioning
confidence: 99%
See 1 more Smart Citation